Chronic Noncommunicable Diseases: a Current Look at the Challenge - Miguel Ángel Serra Valdés (Revista Finlay)
Chronic noncommunicable diseases are currently one of the major challenges facing health systems worldwide given the large number of people affected, their increasing incidence, their gradual contribution to overall mortality, the disability caused by them, and the high cost of hospitalization, medical treatment, and subsequent rehabilitation. Providing quality health services to address these chronic diseases is a priority of institutions and professionals in the field.